Visual aesthetics and user experience: A multiple-session experiment - Sauer, Juergen; Sonderegger, Andreas (International journal of human-computer studies, 2022)
•The seven-week study was aimed at determining the influence of aesthetic appeal and inherent usability of a coffee machine.•The study made use of a wide range of outcome measures, including user performance, perceived usability, perceived attractiveness, emotional distress, and perceived workload.•In contrast to many previous studies, there was no effect of visual aesthetics on user experience.•There was no effect of inherent usability on perceived attractiveness or emotional distress.•The ratings of the coffee machine's visual attractiveness and perceived coffee quality showed no correlation. The article reports a longitudinal lab experiment, in which the influence of product aesthetics and inherent product usability was examined over a period of 7 weeks. Using a 2 × 2 × 7 mixed design, visual aesthetics (high vs. low) and usability (high vs. low) were manipulated as between-subjects variables whereas exposure time was used as a repeated-measures variable. One hundred and ten participants took part in the study, during which they carried out typical tasks of operating a fully automated coffee machine. We measured user experience by using the following outcome variables: perceived usability, perceived attractiveness, performance, affect, workload and perceived coffee quality (gustatory aesthetics). We found no effect of visual aesthetics on user experience (including perceived usability as the chief outcome variable), which is in contrast to a considerable number of previous studies. The absence of such an effect might be associated with influencing factors that have not yet been given sufficient attention (e.g., user identification with product, sensory dominance, characteristics of specific products).